Screening of osmotic stress‐tolerant bacteria for plant growth promotion in wheat (Triticum aestivum L.) and brinjal (Solanum melongena L.) under drought conditions. (10th August 2022) - Patel, P.; Patil, T.; Maiti, S.; Paul, D.; Amaresan, N.
Abstract: Drought stress adversely affects plant growth and productivity. Therefore, the application of plant growth‐promoting bacteria is a viable option for combating drought resistance in crops. In this study, 144 bacteria were isolated from the Kutch desert soil in Gujarat. Based on osmotic stress tolerance and PGP properties, two strains, Bacillus tequilensis (KS5B) and Pseudomonas stutzeri (KS5C) were tested for their effect on wheat ( Triticum aestivum L.) and brinjal ( Solanum melongena L.) under drought stress conditions. Inoculation with osmotic stress‐tolerant bacteria showed 15·15–29·27% enhancement in root length of wheat and 15·27–32·59% in brinjal plants. Similarly, the enhancement of shoot length ranged from 14·72 to 37·70% for wheat and 59·39–95·94% for brinjal plants. Furthermore, the inoculated plants showed significant improvement in chlorophyll content and antioxidant properties such as proline, peroxidase and polyphenol oxidase activity compared to the control. Therefore, the bacterial strains identified in this study can be used to mitigate drought stress and enhance plant biomass. Abstract : Significance and Impact of the Study: Drought stress affects plant biomass and crop yield in arid and semiarid regions worldwide. The threat generated by drought stress must be addressed by improving plant growth under drought stress conditions. The application of osmotic stress‐tolerant bacteria possessing plant growth‐promoting properties is viable, eco‐friendly and cost‐effective. In this study, osmotic stress‐tolerant bacteria improved the growth and biomass of wheat and brinjal under drought stress, and upregulated antioxidant enzymes. This study showed that microbes that mitigate drought stress may be used to enhance crop growth in arid and semiarid soils.